Strategi Promosi Melalui Word of Mouth Terhadap Keputusan Pembelian Konsumen (Studi Kasus UMKM RM Sate Taichan Senayan Palembang) - Siti Komariah Hildayanti; Indah Tri Satriyani (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of promotional strategies through Word of Mouth, along with its components Word of Mouth talkers and Word of Mouth tools on purchasing decisions. This study uses a quantitative descriptive approach by conducting a study on the case of MSME restaurants in the city of Palembang. Data were obtained through questionnaires and interviews with restaurant customers in Palembang City who had implemented Word of Mouth as a promotional strategy, namely the Sate Taichan Sinchan Restaurant located on Jalan Riau, Bukit Besar. The sampling technique was carried out by accident. The number of samples in this study were 178 people. Both WOM Talkers (X1) and WOM Tools (X2) have a positive and significant impact on consumer purchasing decisions (Y). The results of data analysis, the regression coefficient of WOM Talkers (X1) is 26.5% and WOM Tools (X2) is 21.7%. The relationship between WOM Talkers (X1) and WOM Tools (X2) on the consumer purchasing decision variable (Y) has a correlation value of 50.6%. The coefficient of determination (R2) of 25.6% indicates that purchasing decisions (Y) can be explained by WOM Talkers (X1) and WOM Tools (X2), amounting to 25.6% while the rest is explained by other factors. This research was conducted in only one line of business with the object of a restaurant, so that the results of the study could not represent the overall analysis of promotional strategies through WOM on consumer purchasing decisions. For this reason, it is hoped that research can be continued in other sub-sectors of business and industry. This research is expected to enrich the repertoire of knowledge, especially in the discipline of marketing management.